2004
DOI: 10.1021/la0358623
|View full text |Cite
|
Sign up to set email alerts
|

Extremes of Some Foam Properties and Elasticity of Thin Foam Films near the Critical Micelle Concentration

Abstract: The elasticity of open and closed thin foam films is analyzed. The elasticity modulus of a closed film is shown to be additive with respect to contributions from Gibbs elasticity and disjoining pressure. A detailed expression for the film elasticity modulus explains the pronounced maxima of foaminess and foam stability near the critical micelle concentration observed earlier in many experiments. A theory of transversal elasticity of thin foam films is formulated under conditions excluding the action of Gibbs e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…According to this figure, foam stability for nonionic LA-7 surfactant is much more than SDS. As known from literature 32 and as Figure 10 also shows, SDS surfactant solution has the most stable foam at 1 cmc; reducing the SDS concentration below and above the cmc results in the rapid reduction of foam stability; for LA-7 at 0.1 cmc, maximum foam stability is established; and for concentrations other than this point, stability reduces. Marangoni theory explains the higher foam stability at surfactant cmc regions.…”
Section: Resultssupporting
confidence: 60%
“…According to this figure, foam stability for nonionic LA-7 surfactant is much more than SDS. As known from literature 32 and as Figure 10 also shows, SDS surfactant solution has the most stable foam at 1 cmc; reducing the SDS concentration below and above the cmc results in the rapid reduction of foam stability; for LA-7 at 0.1 cmc, maximum foam stability is established; and for concentrations other than this point, stability reduces. Marangoni theory explains the higher foam stability at surfactant cmc regions.…”
Section: Resultssupporting
confidence: 60%
“…The foaming properties of SL-esters and natural SLs with paraffin oil have not yet been reported. surfactant concentration is often attributed to a reduction in interfacial elasticity which reduces foam thin film stability [33]. Results in Figure 4(d) show that, regardless of SL-structure and concentration, the addition of 10% paraffin oil to solutions results in poor foam stabilization.…”
Section: Sophorolipid Ester Foamingmentioning
confidence: 99%
“…These studies have shown CMCs ranging from 20-130 mg/L and mSFT ranging from [32][33][34][35][36][37][38][39][40][41][42] mN/m [10][11][12][13]. Hirata et al studied the initial foaming performance of LSL [11].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of micellar nanostructures has an impact on the properties and the stability of thin liquid films and on systems, which contain them as key ingredients (foams and emulsions) [16,17]. This aspect is closely related to the stability and lifetime of the existing micelles, as well as to the possible reorganization of micellar aggregates in the bulk of the film.…”
Section: Foam Films From Micellar Solutionsmentioning
confidence: 99%